Flavonol and lignan glycosides from Datura metel L. - Mai, Nguyen Thi; Kim Cuc, Nguyen Thi; Quang, Tran Hong; Kiem, Phan Van (Vietnam Journal of Science and Technology, 2017)
Chemical investigation of an acidic methanol extract of the whole plants of D. metel resulted in the isolation of five compounds, including kaempferol 3-O-beta-D-glucosyl(1->2)-beta-D-galactoside 7-O-beta-D-glucoside (1), kaempferol 3-O-beta-glucopyranosyl(1->2)-beta-glucopyranoside-7-O-alpha-rhamnopyranoside (2), pinoresinol O-beta-D-glucopyranoside (3), (7R,8S,7'S,8'R)-4,9,4',7'-tetrahydroxy-3,3'-dimethoxy-7,9'-epoxylignan-4-O-beta-D-glucopyranoside (4), and (7S,8R,7'S,8'S)-4,9,4',7'-tetrahydroxy-3,3'-dimethoxy-7,9'-epoxylignan-4-O-beta-D-glucopyranoside (5). Their structures were elucidated by 1D and 2D NMR and MS spectroscopic analyses as well as comparing with the data reported in the literature. The absolute configurations of compounds 4 and 5 were determined by CD spectra. It is noted that (7R,8S,7'S,8'R)-4,9,4',7'-tetrahydroxy-3,3'-dimethoxy-7,9'-epoxylignan-4-O-beta-D-glucopyranoside and (7S,8R,7'S,8'S)-4,9,4',7'-tetrahydroxy-3,3'-dimethoxy-7,9'-epoxylignan-4-O-beta-D-glucopyranoside were isolated for the first time from the Datura genus.